2016
DOI: 10.1515/for-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

After Obama

Abstract: Barack Obama, the nation's first Black president, is approaching the end of his second and final term. Obama's impending departure raises questions about his legacy. Here we explore what the consequences of the Obama Presidency might be for the future of racial politics in America: for prejudice itself; for the racialization of policy; for the mobilization of the Black vote; and for the racial polarization of the party system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…First, the sample size in 2004 was substantially smaller than in other years and the 2004 survey was the last to be conducted using face‐to‐face interviewer modality alone; later, waves involved mixed methodologies of interviewer‐conducted and respondent‐completed (2008), as well as online (2012 and 2016). The change in methodology may have reduced social desirability bias in responses to racial resentment items (cf., Kinder and Chudy 2016). Second, our measure of sexism differs across models because the ANES included different items across years (see Appendix S1).…”
Section: Discussionmentioning
confidence: 98%
“…First, the sample size in 2004 was substantially smaller than in other years and the 2004 survey was the last to be conducted using face‐to‐face interviewer modality alone; later, waves involved mixed methodologies of interviewer‐conducted and respondent‐completed (2008), as well as online (2012 and 2016). The change in methodology may have reduced social desirability bias in responses to racial resentment items (cf., Kinder and Chudy 2016). Second, our measure of sexism differs across models because the ANES included different items across years (see Appendix S1).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Sears, Citrin, and Kosterman (1987) showed that Jesse Jackson's 1984 campaign for the Democratic Party's presidential nomination immediately accelerated the polarization of Southerner party identification by both racial attitudes and race. And, most importantly for our purposes, Barack Obama's presidency made both race and racial attitudes stronger determinants of several different political evaluations, including vote choice for congress and party identification (Belcher 2016;Hajnal and Lee 2011;Kinder and Chudy 2016;Luttig 2017;Tesler 2013Tesler , 2016.…”
Section: Theoretical Background and Empirical Expectationsmentioning
confidence: 99%
“…1 See Parker (2016) for a comprehensive review and DellaVigna (2010) for an economic analysis. Empirical studies find results in both directions, depending on sample and methodology (for example, Goldman and Mutz (2014); Kinder and Chudy (2016); Tesler and Sears (2010); Tesler (2016)).…”
Section: Introductionmentioning
confidence: 99%